Comparative Study of Antiproliferative Activity in Different Plant Parts of Phaleria macrocarpa and the Underlying Mechanism of Action. (13th June 2022) - Christina, Yuyun Ika; Rifa'i, Muhaimin; Widodo, Nashi; Djati, Muhammad Sasmito
Abstract : Phaleria macrocarpa is a medicinal plant widely used in Indonesian folk medicine to treat several diseases, including cancer. However, the comparative evaluation of various plant parts of P. macrocarpa has not been studied for their anticancer properties on breast cancer. The study aimed to assess the antiproliferative activity of the ethanol extract of various parts of Phaleria macrocarpa against T47D human breast cancer cell lines. Several parts of P. macrocarpa, including pericarp, mesocarp, seed, and leaf, were used to determine the most potent plant part to inhibit the growth of T47D cells. The cytotoxic effects of each plant part were evaluated by WST-1 assay. The apoptotic level of T47D cells was determined by annexin V-FITC-PI and DNA fragmentation assay. Propidium iodide staining and the CFSE assay were used to examine the effect of each extract on cell cycle distribution and cell division, respectively. The relative number of caspase-3, Bax, and Bcl-2 was analyzed by flow cytometry technique. WST-1 assay revealed that P. macrocarpa leaves exhibited the most potent antiproliferative activity (p < 0.05 ) compared to other plant parts with selectivity only to T47D cells. P. macrocarpa leaves extract effectively induced apoptosis, inhibited proliferation, and arrested the cell cycle of T47D cells. The relative number of caspase-3 was significantly (p < 0.05 ) increased after being treated with P. macrocarpa leaf extract. P. macrocarpa leaf extract also leads to the dose-dependent accumulation in the Bax/Bcl-2 ratio due to upregulation of Bax and downregulation of Bcl-2. The overall results indicated that P. macrocarpa leaves could inhibit the proliferation of T47D cells and trigger apoptosis through caspase-3 activation and Bax/Bcl regulation. Therefore, P. macrocarpa leaves can be used for breast cancer therapy.